An Independent Report of the History Experts Committee On the Provincial History of Québec and Canada Program and Approved English Textbooks - Commission scolaire English-Montreal / English Montreal School Board (2018)
In September 2017, the Ministry of Education implemented a revised Secondary III and IV compulsory History of Québec and Canada program. This program raised a number of issues that became of concern to the English Montreal School Board (EMSB). Given these concerns, the EMSB commissioned an independent History Experts Committee to review the content of this program as well as the Ministry-approved English-language textbooks. The following is a summary of the findings of this Committee

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2018)